International Public Sector Accounting Standards (IPSASs): A systematic literature review and future research agenda. (24th June 2020) - Schmidthuber, Lisa; Hilgers, Dennis; Hofmann, Sebastian
Abstract: The development of International Public Sector Accounting Standards (IPSASs) aims at harmonizing public sector accounting at an international level. IPSASs are intended to generate more comparable financial information across national boundaries and minimize differences in countries' generally accepted domestic accounting principles. Despite the various advantages of adopting IPSASs, the new accounting standards have been accompanied by critiques in terms of implementation costs, lack of pressure, and alignment with public sector specialties. In addition, many countries have refused to adapt their governmental accounting systems to IPSASs. In the last two decades, a plethora of studies has investigated the evolution of an internationally comparable accrual‐based accounting system. This article provides a systematic review of this research. First, it identifies existing knowledge of research on IPSASs, resulting in a sample of 80 journal articles. Second, it structures research on IPSASs with an empirical focus in three main research areas: (a) antecedents of IPSAS adoption; (b) implementation of accrual accounting based on IPSASs; and (c) outcomes of IPSAS adoption. Third, it discusses the shortcomings and gaps in the existing research and develops an agenda for future research.